Rh(III)-Catalyzed Synthesis of Isocoumarins via C–H Activation of Phenacyl Phosphoniums with Iodonium Ylides - Jiang, Lu; Gao, Lei; Li, Xiaofei; Shao, Tingting; Yao, Jinzhong; Miao, Maozhong; Zhou, Hongwei (Synthesis, 2023)
A phosphonium-assisted C–H cyclization with iodonium ylides has been developed under redox-neutral rhodium(III) catalysis, offering a wide variety of valuable isocoumarins in moderate to good yields. This transformation proceeds through C–H activation, carbene insertion, and nucleophilic addition processes. The reaction occurs under a low catalyst loading in a short reaction time and does not require an oxidant.
Keywords: rhodium; isocoumarins; phenacyl phosphoniums; iodonium ylides; C–H activation